Developing antioxidant of gold nanofilm by a facile electrodeposition method - Setia Budi; Babay Asih Suliasih; Ibrahim Dhuafa Fikri; Afrizal; Marissa Angelina (Journal of Advanced Pharmaceutical Technology & Research)
Antioxidant activity of gold nanoparticles (AuNPs) is known to have considerable therapeutic benefits in the field of medicine. This study aimed to synthesize AuNPs in the form of gold nanofilms (AuNFs) and characterize their antioxidant activity by controlling preparation parameters of scan rate. The AuNFs were synthesized by cyclic voltammetry technique by varying scan rates. The antioxidant capacity was measured using in vitro 2,2-diphenyl-1-picrylhydrazyl assay. The effect of incubation time on the assay was also observed by varying the incubation periods to 30, 45, 60, 75, and 90 min. Antioxidant activity of AuNPs gradually increased from 15.18% ±1.8% to 46.17% ±1.87% with the increase in the scan rate. The examination of the variation in incubation time reveals that all samples exhibited a slight increase of inhibition percentage that ranged from 0.47 to 2.17 for each incubation time. This phenomenon showed that the generated AuNFs are classified as slow hydrogen atom transfer. The AuNFs synthesized using the cyclic voltammetry technique exhibited significant antioxidant activity, which was influenced by the scan rate factor. In addition, based on the analysis of incubation time variation, these AuNFs demonstrated a slow hydrogen atom transfer in relation to their reaction kinetics with free radicals.